EXTRACELLULAR POLYSACCHARIDES OF AZOTOBACTER VINELANDII - Cohen, Gary H. (1964)
Cohen, Gary H. (University of Vermont, Burlington), and Donald B. Johnstone. Extracellular polysaccharides of Azotobacter vinelandii. J. Bacteriol. 88:329–338. 1964.—Extracellular polysaccharides synthetized by Azotobacter vinelandii strains 155, 102, and 3A were shown to be carboxylic acid heteropolysaccharides of apparent high molecular weight. Cells were grown in a nitrogen-free, mineral broth medium with 2% sucrose. Extracellular slime was recovered by centrifugation and purified by repeated alcohol precipitation and Sevag deproteinization. Capsular polysaccharide was recovered from washed cells by mild alkaline digestion. Methods of isolation and purification appeared to provide polysaccharide showing no evidence of heterogeneity when examined by chemical and physical methods. Infrared analysis of purified slime from the three strains suggested fundamental structural similarities. Colorimetric, paper chromatographic, and enzymatic analyses on both intact and acid-hydrolyzed slime polysaccharide indicated that the polymers contained in common galacturonic acid, [α] d-glucose, and rhamnose at a ratio of approximately 43:2:1, as well as a hexuronic acid lactone, probably mannurono-lactone. However, as shown by chemical and infrared analysis, minor differences did exist; namely, slime from strain 155 and 102 contained o-acetyl groups, whereas slime from strain 3A contained none. A sialic acid-like component (1.5% of dry weight of the polysaccharide, calculated as N-acetyl neuraminic acid), was found only in the slime of strain 155. Capsular polysaccharide composition closely resembled that for slime. It is of interest that the major slime components were identical whether the energy source provided for the cells was sucrose, glucose, fructose, or ethanol.